Cardiovascular risk profile in Olympic athletes: an unexpected and underestimated risk scenario. Issue 1 (10th January 2019) - D'Ascenzi, Flavio; Caselli, Stefano; Alvino, Federico; Digiacinto, Barbara; Lemme, Erika; Piepoli, Massimo; Pelliccia, Antonio
Abstract : Background: Prevalence of cardiovascular (CV) risk factors has been poorly explored in subjects regularly engaged in high-intensity exercise programmes. Our aim was, therefore, to assess the prevalence and distribution of CV risk factors in a large population of competitive athletes, to derive the characteristics of athlete's lifestyle associated with the best CV profile. Methods: 1058 Olympic athletes (656 males, 402 females), consecutively evaluated in the period 2014–2016, represent the study population. Prevalence and distribution of CV risk factors was assessed, in relation to age, body size and sport. Findings: Dyslipidemia was the most common risk (32%), followed by increased waist circumference (25%), positive family history (18%), smoking habit (8%), hypertension (3.8%) and hyperglycaemia (0.3%). Large subset of athletes (418, 40%) had none or 1 (414, 39%) risk factor, while only a few (39, 3.7%) had 3/4 CV risk factors. The group without risks largely comprised endurance athletes (34%). Ageing was associated with higher total and low-density lipoprotein cholesterol, triglycerides (p<0.001) and glycaemia (p=0.002) and lower high-density lipoprotein cholesterol. On multivariate logistic regression analysis, age, BMI and body fat were identified as independent predictors of increased CV risk. Interpretation: Dyslipidemia and increased waist circumference are common in elite athletes (32% and 25%, respectively). A large proportion (40%) of athletes, mostly endurance, are totally free from risk factors. Only a minority (3%) presents a high CV risk, largely expression of lifestyle and related to modifiable CV risk factors.